Sistem Pendukung Keputusan Pemilihan Ketua Pam Gki Sion Sanggeng Menggunakan Metode SMART: Decision Support System for the Election of the Chairman of Pam Gki Sion Sanggeng Using the SMART Method - gladys sawaki sawaki; Lion Ferdinan Marini; Marlinda Sanglise (Universitas Papua, 2023)
Manokwari Regency has an area of 3,168.28 km² with various kinds of Church denominations in this district, one of the old church denominations in Tanah Papua, especially the Manokwari district, namely the Bible Christian Church which has elements of PAM (Young Members Association) in it. The election of the PAM Chairperson at the Sanggeng Zion Congregational Bible Christian Church is still relatively manual, for this reason this study aims to create a Decision Making System for the Selection of PAM Chairpersons based on existing criteria. This study uses the SMART method with stages, namely each criterion is ranked based on the level of importance. Then given a weight so that the normalized value can be calculated. In order to evaluate the expected alternatives, single attribute utilities are calculated so that the resulting output is a decision support system in the form of a ranking with the order of the greatest value. This application is designed using the PHP and MySQL programming languages. The results obtained from this study were that Sister Febby Tulaseket became Chair of PAM with the highest score of 00.1 to be recommended as Chair of PAM at GKI Sion Sanggeng Manokwari.